Peningkatan Literasi Dan Numerasi Melalui Pendampingan Kampus Mengajar 6 Di SDN Tamansari 01 - Arayna Azizatul Milla; Astri Widyaruli Anggraeni (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
This service was carried out because of the Teaching Campus 6 activities. This activity is one of the MBKM (Free Learning Campus Independent) programs. This program aims to increase students' interest in learning and increase student literacy and numeracy. If you pay attention nowadays, students' literacy and numeracy are really decreasing, they can even be said to be less effective. This problem can affect the effectiveness of the learning process, one of which is at SDN Tamansari 01. The method used is to familiarize students with literacy and numeracy during learning. The final result of this activity is getting used to literacy and implementing AKM in order to see abilities and measure student learning outcomes.